Developmental and interactional aspects of young EFL learners’ self-concept - Mihaljević-Djigunović, Jelena (Array, 2014)
The chapter describes a study which shows that young learners' self-concept is not a stable learner factor. Its dynamic and complex nature is reflected in its inter- as well as intra- learner variability and in different interactions with other learner characteristics and contextual factors.